The Impact of Well-being Oriented HRM on Employees Happiness: The Mediating Role of Internal CSR - Mubbashar, Nadia; Shah, Dr Muzammel; Mubbashar Qayyum (UW Journal of Management Sciences, 2025)
Purpose: Despite the popularity of the research on Human Resource Management (HRM), little is known about the studies that concentrate on well-being-oriented HRM (WBHRM). The proposed study seeks to understand the effect of WBHRM on employee happiness and how internal Corporate Social Responsibility (CSR) mediates that effect. Design and Methodology: This was quantitative research that utilized survey method in gathering data of 404 employees in different divisions of the banking industry within Islamabad, Pakistan. The hypothesized relationships were analyzed using Structural Equation Modeling (SEM). Findings: The findings point out that WBHRM does not directly affect employee happiness. Nonetheless, the effect of WBHRM on internal CSR is significant, and the latter has a positive impact on the happiness of employees. Accordingly, the connection between WBHRM and employee happiness is completely mediated by internal CSR. Originality/Value: The study adds to the scarcely populated literature that relates WBHRM, internal CSR, and employee happiness. Through the application of Conservation of Resources (COR) theory, the study shows that supportive HRM practices can make employees feel appreciated and involved in a resource-rich environment, which contributes to employee happiness. Practical Implications: The WBHRM practices that organizations ought to invest in according to internal CSR values would help create a conducive workplace, especially in service industries such as banking. By supporting the whole well-being of employees, it is possible to enhance their satisfaction and make the process of fulfilling organizational purposes more successful.